(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
The concept of human dignity plays a role in our contemporary societies, in that it serves as an essential foundation of human rights. However, today we are far from having found a reasonable basis on which to justify that special value we attribute to humans. As a consequence, movements that criticize the idea of human dignity have proliferated, proposing alternative axiological systems. In this text, we will study, firstly, the effective strength of both the anthropocentric model that is built on the belief in human dignity and the solvency of the main alternatives proposed. In conclusion, the suitability of re-constructing a weak anthropocentric model will be shown following the guidelines already indicated by Engelhardt in the last century.